Personalized and Regenerative Medicine for Liver Diseases - Giri, Shibashish; Bader, Augustinus (Current Stem Cell Research & Therapy, 2016)
Regeneration of diseased organ is a ubiquitous clinical need. The clinical utilities of adult stem cells and microRNA have become a promising strategy for treatment of a number disease. This review aims to highlight the current clinical evidence of personalized and regenerative therapy for diseases like liver which could revolutionize patient care in the near future at a global scale. Herein, we explain the importance of personalized and regenerative medicine for bedside (intraoperative) in situ and In vivo regeneration of damaged organ/ tissues that is now being transferred to a larger field of clinical applications in a novel translational approach.
Keywords: bioartificial liver